Kinerja Aktivasi dan Impregnasi Fly Ash sebagai Adsorben Fenol - Fatimah; Hardianti, Siti; Octaviannus, Stephen (Talenta Publisher (Universitas Sumatera Utara), 2021)
The purpose of this study was to determine the response and performance of fly ash as an adsorbent activated by HCl and impregnated with FeCl3 to absorb phenol. In this study, the fly ash activation process was carried out using 8 M HCl for 2 hours and impregnated with 2% FeCl3 for 2 hours. Activated and impregnated fly ash was analyzed using a Scanning Electron Microscope-Energy Dispersive Spectrophotometer (SEM-EDX). The results of the activated and impregnated fly ash surface using SEM-EDX showed that there were changes in morphology and functional groups. Then activated and impregnated fly ash was used to absorb phenol at a time variation of 60 minutes, 120 minutes, 180 minutes, 240 minutes and 300 minutes. At 180 minutes of contact time, the equilibrium point is obtained with an absorption efficiency of 90.5%. Second-order pseudo kinetics were used for phenol adsorption by Fe+ impregnated fly ash (R2 = 0.9916). The isotherm models used in the phenol adsorption process by fly ash impregnated with Fe+ are Langmuir Isotherm (R2 = 0.9927) and Freundlich Isotherm (R2 = 0.9984), which means that the adsorption process occurs in multi-layer and mono-layers.